Religie als instrument? Over de desecularising van de ontwikkelingssamenwerking - Berenschot, Ward; Tieleman, Henk (Religie & Samenleving, 2009)
Religion is gaining prominence in the Dutch international development sector. This article discusses some of the assumptions behind the growing conviction that religion can also be part of the solution for various developmental ills. Using the Hindu-Muslim violence that occurred in Gujarat (India) in 2002 as a case study to reflect on the ambivalent role that religion plays in development-processes, we argue that the engagement with religion in the international development sector should go beyond seeing religion as an instrument to pursue secular goals.